The axial force influence on the flexibility of steel joints subject to bending under fully developed fire conditions - Maślak, Mariusz; Snela, Małgorzata (Budownictwo i Architektura / Civil and Architectural Engineering, 2014)
The axial force qualitative influence as well as its quantitative evaluation on the behaviour of the flexible steel beam-to-beam and column-to-column knee joints subject to bending under fire conditions are assessed and discussed in detail. The proposed calculation algorithm is based on the generalization of classical component method. The essential effect of such axial force is not only the correction of internal forces applied to particular joint components, but also the significant modification of their strain conditions.